2016
DOI: 10.1007/s13277-016-5248-y
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase (NEP) is differentially involved in biological activities and cell signaling of colon cancer cell lines derived from various stages of tumor development

Abstract: The presented studies were aimed at exploring the role of neutral endopeptidase (NEP) in the function of colon cancer cell lines LS 180 and SW 620, derived from different grades and stages of tumor development. NEP silencing by siRNA resulted in decreased viability and proliferation accompanied by increased apoptosis in both cell lines. Additionally, cell cycle arrest at the G2/M phase was observed, but only in LS 180 cells. Opposite to these results, serum-stimulated migration was increased in both cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
8
3
Order By: Relevance
“…However, in SW480 CD10-, there was no significant difference in cell viability (Figure 2A). Our results can be compared to those obtained by Mizerska-Kowalska et al, who have also observed a reduced proliferation (determined by the BrdU method) and increased proportion of apoptotic cells following CD10 knockdown in the CRC cell line LS180 (Mizerska-Kowalska et al 2016).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…However, in SW480 CD10-, there was no significant difference in cell viability (Figure 2A). Our results can be compared to those obtained by Mizerska-Kowalska et al, who have also observed a reduced proliferation (determined by the BrdU method) and increased proportion of apoptotic cells following CD10 knockdown in the CRC cell line LS180 (Mizerska-Kowalska et al 2016).…”
Section: Discussionsupporting
confidence: 76%
“…In their case however, cell cycle analysis showed G2/M arrest upon transient CD10 knockdown in LS180 cells but not in SW620 (Mizerska-Kowalska et al 2016). In contrast, although we have observed the same net effect on proliferation following CD10 knockdown, we have obtained a small but significant decrease in G2/M.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations